(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
An analysis is presented to investigate the Hall and Ion-slip effects on non-Newtonian couple stress fluid flow between vertical channel in the presence of thermophoresis phenomena. The considered fluid obeys to the viscoelastic second-grade model. The problem is modulated mathematically to describe continuity, momentum, temperature, and concentration equations. The influences of physical parameters of dimensionless equations of velocity components () and (), temperature () and concentration () have been shown in some of figuthe res, as well as skin friction (), Nusselt number() and Sherwood number() have been computed. It is found that the velocity decreases with increasing in Hall parameter and Ion slip parameters.